2018
DOI: 10.1186/s12951-018-0360-3
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte-targeted and 17β-estradiol-loaded acoustic nanoprobes as a theranostic platform for cardiac hypertrophy

Abstract: BackgroundTheranostic perfluorocarbon nanoprobes have recently attracted attention due to their fascinating versatility in integrating diagnostics and therapeutics into a single system. Furthermore, although 17β-estradiol (E2) is a potential anti-hypertrophic drug, it has severe non-specific adverse effects in various organs. Therefore, we have developed cardiomyocyte-targeted theranostic nanoprobes to achieve concurrent targeted imaging and treatment of cardiac hypertrophy.ResultsWe had successfully synthesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…The strong PCM-MSN signal distributed in the mouse heart, which was threefold weaker in the control animals, suggested that PCM had efficiently guided nanoparticles to the heart. Thus it enhanced tissue-specific uptake of MSN as consistent with previous publications [ 15 , 16 , 29 , 30 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The strong PCM-MSN signal distributed in the mouse heart, which was threefold weaker in the control animals, suggested that PCM had efficiently guided nanoparticles to the heart. Thus it enhanced tissue-specific uptake of MSN as consistent with previous publications [ 15 , 16 , 29 , 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…PCM, a 20-mer peptide (WLSEAGPVVTVRALRGTGSW) isolated by phage display, could bind to primary cardiomyocytes with a 180-fold higher efficiency than the control, at the same time showing great specificity [ 15 ]. Therapeutic ultrasound, known as low-intensity focused ultrasound (LIFU), has been recommended as an efficient approach to further improve targeted delivery to the myocardium [ 16 , 17 ]. When exposed to the LIFU irradiation, the uptake of bioactive agents was enhanced in specific tissues due to a transient increase in the cell membrane permeability [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nanodroplets (NDs) are nanometric structures typically consisting of an external layer (e.g., polymeric PLGA-COOH), and an internal core (e.g., liquid dichloromethane (CH 2 Cl 2 ),) which can transform into MBs under the application of ultrasound through a mechanism called acoustic droplet vaporization (ADV). As for NBs and MBs, NDs can be associated with molecules of interest for the treatment of heart diseases such as primary cardiomyocytes (PCMs) or 17β-estradiol (E2), which are drugs recommended for cardiac hypertrophy treatment [42]. When such NDs were injected intravenously into rats followed by the application of ultrasound in the heart region, it yielded both the release of E2 from NDs, and ND imaging following ND expansion into MB, highlighting a mechanism of ND use as a theragnostic compound for the treatment/detection of cardiac disease [42].…”
Section: Various Types Of Nanomaterials Used As Theragnostic Ultrasou...mentioning
confidence: 99%
“…As for NBs and MBs, NDs can be associated with molecules of interest for the treatment of heart diseases such as primary cardiomyocytes (PCMs) or 17β-estradiol (E2), which are drugs recommended for cardiac hypertrophy treatment [42]. When such NDs were injected intravenously into rats followed by the application of ultrasound in the heart region, it yielded both the release of E2 from NDs, and ND imaging following ND expansion into MB, highlighting a mechanism of ND use as a theragnostic compound for the treatment/detection of cardiac disease [42]. Other NDs encapsulating PFP liquid, which were labelled with a CNA35 targeting myocardial scar, could passively diffuse toward the fibrotic myocardium due to their small size, and transform into gaseous MBs under ultrasound application, enabling myocardial infarction detection [42].…”
Section: Various Types Of Nanomaterials Used As Theragnostic Ultrasou...mentioning
confidence: 99%
“…PLGA polymers can be prepared in almost any size and morphology as well as modified into hydrophilic and hydrophobic molecules of almost any size; therefore, they are widely used for drug delivery. Polymeric materials with good biocompatibility have been used to construct nanoparticles for the specific targeted delivery of drugs or as contrast agents for detecting tumors [ 15 , 16 ], as well as cardiovascular [ 17 , 18 ], neurological [ 19 , 20 ], and other diseases. Based on the low immunogenicity of polyethylene glycol (PEG) [ 21 ], PLGA-PEG, a block co-polymer, is more suitable for vivo experiments than PLGA alone [ 22 ].…”
Section: Introductionmentioning
confidence: 99%